Peranan “Yang Lain” dalam Membentuk Karakter Petugas Pastoral Berdasarkan Ensiklik “Fratelli Tutti” Sri Paus Fransiskus - Paulus Tolo (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
The third encyclic written by Pope Francis is Fratelli Tutti. The title of the encyclic is taken from admonitio of St. Francis of Asisi. Literally Fratelli Tutti means all brothers. As far as the content of the encyclic is concerned, it is considered as a social encyclic. It speaks about the concern of the Pope on social issues especially human relations. In the Pope’s view, there are signs of disruption in human relation especially relation with “others”. So in the first place a summary of the encyclic will be presented. In the second place, the author of this article points out the role of “others” in the context of human development. The other plays an important role for reaching an integral human person. For pastors, the role of “other” in his ministries and services helps him to change his attitude and mentality. This article tries to demonstrate that the most tangible way the “other” can do to pastors is urging them to have a radical conversion. The “other” challenges pastors to make decision to be a neighbour for the “other”.